Powered by the People. Human-Powered Energy Generation as Lifestyle Choice - Andreas Sicklinger; Adrian Peach (Pad)
The problem of energy consumption, resource depletion and global warming has moved in fifty years from a fringe campaign to the mainstream of politics, scientific research and the media. However, the need to reduce consumption conflicts inexorably with the lifestyle demands of consumers who continue to buy more, use more and waste more, and who are growing in number in the world’s emerging economies. This paper documents an investigation into the following research questions: How can we as designers turn the need to reduce energy and resource consumption into an attractive lifestyle proposition? Could we exploit the increased interest of consumers in health and sporting activity by harnessing their body energy to drive appliances? Could we turn this into a win-win proposition? The investigation took the form of two design development workshops at the University of Bologna in 2022 involving 60 participants. Drawing inspiration from the wake-up calls of 20th Century Modernism and the designer activist Victor Papanek circa 1970, concerned with provoking mass behavioral change for societal benefit, participants were tasked with developing product proposals to generate decentralized energy and store it for use in the home, office or community. The activities culminated in a panel discussion of experts in the field, who expressed their own view based on the workshop input, offering their own speculative reflections. The challenge for designers within such a process is to propose the initiative as a positive lifestyle choice, to be embraced willingly by consumers and citizens in order to bring about a shift in awareness and habits.